Statins as anti-inflammatory agents in atherogenesis: molecular mechanisms and lessons from the recent clinical trials. - Antonopoulos, A; Margaritis, M; Lee, R; Channon, K; Antoniades, C (2012)
Ample evidence exists in support of the potent anti-inflammatory properties of statins. In cell studies and animal models statins exert beneficial cardiovascular effects. By inhibiting intracellular isoprenoids formation, statins suppress vascular and myocardial inflammation, favorably modulate vascular and myocardial redox state and improve nitric oxide bioavailability. Randomized clinical trials have demonstrated that further to their lipid lowering effects, statins are useful in the primary and secondary prevention of coronary heart disease (CHD) due to their anti-inflammatory potential. The landmark JUPITER trial suggested that in subjects without CHD, suppression of low-grade inflammation by statins improves clinical outcome. However, recent trials have failed to document any clinical benefit with statins in high risk groups, such in heart failure or chronic kidney disease patients. In this review, we aim to summarize the existing evidence on statins as an anti-inflammatory agent in atherogenesis. We describe the molecular mechanisms responsible for the antiinflammatory effects of statins, as well as clinical data on the non lipid-lowering, anti-inflammatory effects of statins on cardiovascular outcomes. Lastly, the controversy of the recent large randomized clinical trials and the issue of statin withdrawal are also discussed.